Intractable intraoperative bleeding requiring platelet transfusion during emergent cholecystectomy in a patient with dual antiplatelet therapy after drug-eluting coronary stent implantation (with video). (26th March 2013) - Fujikawa, Takahisa; Noda, Tomohiro; Tada, Seiichiro; Tanaka, Akira
Abstract : We report a case of a 76-year-old man, receiving dual antiplatelet therapy (DAPT) with aspirin and ticlopidine for the past 6 years after implantation of drug-eluting coronary stent, developed a severe hypochondriac pain. After diagnosing severe acute cholecystitis by an enhanced CT, emergent laparotomy under continuation of DAPT was attempted. During the operation, intractable bleeding from the adhesiolysed liver surface was encountered, which required platelet transfusion. Subtotal cholecystectomy with abdominal drainage was performed, and the patient recovered without any postoperative bleeding or thromboembolic complications. Like the present case, the final decision should be made to perform platelet transfusion when life-threatening DAPT-induced intraoperative bleeding occurs during an emergent surgery, despite the elevated risk of stent thrombosis.